Synthesis, structure and reactivity of sulfur-rich [Fe(L-1)(L-2)('tpS(4)')] complexes with rigid [Fe('tpS(4)'] cores and sigma-pi Co-ligands ('tpS(4)'(2-)=1,2-bis(2-mercaptophenylthio)phenylene(2-); L-1, L-2=CO, PR3, NO) - Sellmann, Dieter; Blum, David; Heinemann, Frank Wilhelm; Sutter, Jörg (European Journal of Inorganic Chemistry, 2003)
Optimisation of synthesis and purification steps has made the new ligand 'tPS(4)'(2-) available in preparative amounts. Treatment of FeCl(2)(.)4H(2)O with 'tPS(4)'-Li-2 or 'tPS(4)'-Na-2 yielded [Fe('tPS(4)')] (1), which in the solid state and in the absence of co-ligands probably trimerises to give paramagnetic [Fe('tPS(4)')](3). The [Fe('tPS(4)')] fragment displays helical coordination of the 'tPS(4)'(2-) ligand and binds sigma-pi ligands such as CO, NO and phosphanes to give diamagnetic 18-valence-electron complexes of general formula [Fe(L-1)(L-2) ('tPS(4)')]The cis-dicarbonyl complex [Fe(CO)(2)CtPS(4)')1 (2) is labile and readily dissociates CO to give dinuclear [Fe(CO)('tPS(4)')](2) (3). Simultaneous coordination of CO and phosphanes yielded [Fe(CO)(PR3)('tPS(4)')] with R = Me (4), Et (5), Pr (6) and Bu (7), but it proved impossible to obtain analogous complexes with bulky PPh3 or PCY3 ligands. Bis(phosphane) complexes could be obtained only with PMe3 and the bidentate dppe, which yielded [Fe(PMe3)(2)('tPS(4)')] (8) and [Fe(dppe)('tPS4')] (11). Alkylphosphanes with longer alkyl substituents, such as PnPr(3) and PnBu(3), gave the labile derivatives [Fe(PR3)(2)-('tPS(4)')] with R = nPr (9) and nBu (10). Complexes 9 and 10 reversibly dissociate one PR3 ligand, yielding diamagnetic [Fe(PR3)(WtPS(4)')] fragments. These findings explain the decisive and hitherto inexplicable influence of PPr3 and PBu3 ligands upon the stabilisation of N2H2 in the diazene complexes [mu-N2H2Fe(PR3)('tpS(4)')(2)] with R = Pr, Bu. Treatment of [Fe('tPS(4)')] (1) or [Fe(CO)('tPS(4)')](2) (3) with NO or NO+ yielded [Fe(NO)(2)('tPS(4)')] (12). The molecular structures of 3, 4, 7 and 8 were determined by X-ray structure analysis. Spectroscopic and structural results indicate that the differences in reactivity between [Fe(L-1)(L-2) ('tPS(4)')] and homologous [Fe(L-1)(L-2)('S-4')] complexes can be traced back to subtle electronic and structural effects. (C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003
Keywords: helical structures; iron; S ligands